Use of a Low Dose of Equine Purified FSH to Induce Multiple Ovulations in Mares - Araujo, G. H. M. [UNESP]; Rocha Filho, A. N. [UNESP]; Lopes, E. P.; Moya, C. F. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The effects of a low dose of equine purified FSH (eFSH) on incidence of multiple ovulations and embryo recovery rate in mares were studied. During the physiological breeding season in Brazil (19 degrees 45'45'S), 14 Mangalarga Marchador donor mares were used in a crossover study and another 25 mares of the same breed, between 3 years and 12 years of age were used as recipients for the embryo transfers. Donors were monitored during two consecutive oestrus cycles, an untreated control cycle followed by a treated cycle, when eFSH was administered. In both cycles, after an embryo collection attempt on day 8 post-ovulation all mares received 7.5 mg dinoprost and had their two largest follicles tracked daily by ultrasonography until the period of ovulation. Mares were inseminated every 48 h with extended fresh semen from a single stallion after the identification of a 35-mm follicle until the period of ovulation. Ovulations were induced by intravenous administration of 2.500 IU of human chorionic gonadotropin, upon detection of a 35- to 40-mm follicle. In the treated cycle, 5 mg eFSH was given intramuscularly once a day, from day 8 post previous ovulation until at least one follicle reached 35 mm in diameter. Embryo flushes were performed on day 8 of dioestrus (day 0 = ovulation). Treatment with eFSH resulted in higher (p < 0.05) ovulation rate and incidence of multiple ovulations compared to the control (1.6 vs 1.0 and 50% vs 0%, respectively - one mare had triple ovulation). However, embryo recovery rates in the control and treated cycles were similar (0.8 and 1.0, respectively; p > 0.05). Pregnancy rates in the recipient mares following embryo transfer were similar for the control and eFSH cycles (11/11 and 10/14, respectively). Additional studies are necessary in order to develop a low-dose protocol for the use of eFSH that brings a more consistent contribution to the efficiency of commercial equine embryo transfer programs.